Dispatches - Herr, Michael (London : Pan Macmillan, 2015)
A seminal classic of war reportage.
Breathing in -- Hell sucks -- Khe Sanh -- Illumination rounds -- Colleagues -- Breathing out.
ENH
Keywords: Herr, Michael, -- 1940-2016; Vietnam War, (1961-1975) -- Personal narratives -- American; English literature